PENGARUH NILAI PELANGGAN, KEDEKATAN EMOSIONAL DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA BANKALTIMTARA UNIT USAHA SYARIAH SAMARINDA - Zulfikar Zulfikar; Nyoria Anggraeni Mersa; Annisa Putri; Febby Veronica Tjong (Politeknik Negeri Samarinda, 2021)
This research aims to determine the effect of the Customer Value, the Emotional Approach and the Service Quality on the Customer Statisfaction at Bankaltimtara Unit Usaha Syariah in Samarinda. The analytical tools used in this research is multiple liniear regression analysis. The result of multiple liniear regression analysis the equation that was Y = 0,512 + 0,184 X1 + 0,134 X2 +0,592 X3. The Customer Value value is 0,184, the Emotional Approach value is 0,134 an the Service Quality value is 0,592. The result of this research indicated that the variables of the Customer Value, the Emotional Approach and the Service Quality partially or simultaneously here a positive and significant impact on the Customer Statisfaction at Bankaltimtara Unit Usaha Syariah in Samarinda.